2017
DOI: 10.21767/2471-299x.1000049
|View full text |Cite
|
Sign up to set email alerts
|

Management and Education in Patients with Diabetes Mellitus

Abstract: Patients with Diabetes Mellitus (DM) can actively participate in the management of this disease, with therapeutic education playing an essential role in the optimization of knowledge, resources and skills required to achieve targets of metabolic control, reduce the onset of acute and chronic complications, and preserve quality of life. In this context, the management of DM becomes a holistic endeavor, by promoting the reasonable use of therapeutic resources by the patient's themselvesinvolving self-management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(19 reference statements)
0
13
0
4
Order By: Relevance
“…Several studies have demonstrated how diet education improved patients’ knowledge and helped them adopt healthier behaviors [15,16,17,18,19,20,21,22,23]. In this study, after the education, participants adhered to a recommended diet and meal planning significantly more and had better knowledge regarding foods that increase blood glucose.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Several studies have demonstrated how diet education improved patients’ knowledge and helped them adopt healthier behaviors [15,16,17,18,19,20,21,22,23]. In this study, after the education, participants adhered to a recommended diet and meal planning significantly more and had better knowledge regarding foods that increase blood glucose.…”
Section: Discussionmentioning
confidence: 63%
“…A similar study carried out in Brazil also showed a significant increase in the level of knowledge of subjects about their disease, particularly regarding knowledge on nutrition [15]. Education contributes to more effective glycemia control and reduces disease complications [16]. Self-care knowledge levels were found to be significantly associated with previous health education about diabetes [17].…”
Section: Discussionmentioning
confidence: 95%
“…When analyzing some of the nursing theories, it is evident that care of patients with NCDs such as DM can be improved by means of educational action (Figure 1). For the person with DM, educational support is vital because they need help in decision making, acquisition of skills and abilities as well as counsel for the control of positive and encouraging behaviors, incorporating them into their self-care, which guarantees therapeutic adherence [17]. However, recent studies seem to suggest that there is a gap between knowledge, attitude and practice, so that even if theoretical knowledge exists, the attitude of people and health professionals may influence positively of neutralize the carrying out of practice changes that improve the quality of life.…”
Section: Nursing Care In Diabetes Mellitusmentioning
confidence: 99%
“…To achieve effectiveness and efficiency in DE´ management [16,17] people must be included in a long term therapeutic alliance in which self-management and glycemic control (individualized metabolic control goals) can positively affect life quality and reduce the risk of condition-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Other important step at the primary care level will be implementing good diabetes self-management education programs with emphasis on motivating good self-care behaviours especially lifestyle modification (3). But the success is on sustaining the healthy behaviour which definitely need periodic reinforcement, adequate social support systems such as allied health care workers, support groups, etc.…”
mentioning
confidence: 99%